Maintained diabetes remission among normal BMI individuals achieved without ongoing intervention: a three-year follow-up study of intermittent calorie restriction - Wu, Ruiyu; Yang, Xiao; Zhou, Xu; Xiao, Zhiyong; Chen, Xuan; Zhou, Jiali; Li, Jian; Yin, Zhuoming; Lai, Xihu; Wang, Tao; Li, Quanmin; Liu, Dongbo (Frontiers in Endocrinology, 2026)
ObjectiveEven when diabetes remission is achieved and maintained through weight loss, relapse is likely if body weight and consequently BMI increase again. This study aims to evaluate the maintenance of remission without ongoing intervention among participants who achieved diabetes remission and normal BMI through intermittent energy restriction.Research design and methodsThis study was a randomized controlled trial with parallel-design and open-label. The intervention group received a three-month Chinese Medical Nutrition Therapy (CMNT) diet intervention consisting of six 15-day cycles. Each cycle encompassed five consecutive days of energy restriction (840 kcal/day), succeeded by 10 days of ad libitum eating. During the ad libitum dietary phase and the subsequent 3-year follow-up, participants self-selected food according to the Chinese Dietary Guidelines for Diabetes (2017 edition). Eventually, their HbA1c, fasting blood glucose (FBG), antidiabetic medication use, weight, quality of life, and complications were assessed.ResultsAfter 3 years of follow-up, 75% of participants in the CMNT group maintained diabetes remission compared to none in the control group. The maintenance of remission was found to be positively correlated with the extent of withdrawal of insulin or insulinotropic agent through the intervention. However, for people whose BMI is below 24 kg/m², regaining weight did not affect the maintenance of remission. Additionally, the CMNT group exhibited significant improvements in quality of life, along with lower rates of complications, hospitalizations, and all-cause mortality.ConclusionFor individuals with normal BMI, after following a three-month CMNT, diabetes remission is observed over three years without ongoing structured maintenance.Clinical Trial Registrychictr.org.cn, identifier ChiCTR2000038036.